State-Level Support for Tobacco 21 Laws: Results of a Five-State Survey. Issue 11 (15th September 2017) - Morain, Stephanie R; Garson, Arthur; Raphael, Jean L
Abstract: Introduction: Legal strategies to raise the minimum age of purchase for tobacco from 18 to 21, known as "Tobacco 21 laws" are a promising means to reduce adolescent tobacco initiation and use. Tobacco 21 laws are enacted at the local and state level, yet prior studies have examined national support. To address this gap, we assessed attitudes of residents in five states toward Tobacco 21 laws, and how attitudes varied by demographic, political, and health status characteristics. Methods: The data are derived from the 2016 Texas Medical Center (TMC) Consumer Health Report, a survey of 5007 adults from five states: California, Florida, Ohio, New York, and Texas. Bivariate and multivariate logistic regression analyses were used to assess differences in support. Results: Eight in 10 respondents supported Tobacco 21. Support was high across all five states, ranging from 78% in Texas to 85% in New York. Tobacco 21 was supported by a majority of respondents in all racial, educational, age, and income groups assessed. While support was generally strong, chi-square analyses revealed differences across states in support by demographic and health status characteristics. Support was generally higher among older individuals, whites, and those with more education, although the size and even direction of the relationship by population subgroup varied across states. Conclusion: Tobacco 21 laws enjoy overwhelming majority support in all five states and across all sociodemographic subgroups assessed. However, the strength of support by population subgroup varies across states. Implications: While earlier studies had found strong support for Tobacco 21 laws at the national level, little data were available about attitudes at the state level, where current Tobacco 21 policymaking efforts are concentrated. Our data indicate that legislators from both liberal and conservative states should feel confident in advancing Tobacco 21 laws to protect the current and future health of adolescents. However, patterns of support vary by population subgroup across states. Understanding variations in support by population subgroup at the state level can guide policymakers in targeted efforts to advance public health laws aimed at reducing adolescent tobacco initiation and use.